Avaliação de plano radioterápico conformacional 3D de próstata no sistema de planejamento XiO®: variação de parâmetros radiométricos e algoritmos de cálculo - Bérgamo, Danilo Augusto [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Along the technological advances in radiotherapy planning techniques, sophisticated methods of deposition of doses simulation, which are based on calculation algorithms from Treatment Planning Systems (TPS), arise. It is important the active medical physicists in the area keep updated in new processes and technologies linked to TPS. Prostate cancer is currently listed as the second most frequent type of cancer throughout the male population in the world and 3D conformal radiotherapy is commonly used to treat these cases. The objective of this study was to evaluate different conformational radiotherapy planning 3D in prostate cases, varying radiometric parameters and calculation algorithms which were developed in TPS XiO® and designed by Elekta. From a single clinical selected case of prostate cancer two planning techniques with 5 and 6 fields were developed, and for each one the energy (6 MV and 10 MV) and the dose calculation algorithm (Superposition and Convolution) were varied, totaling eight different plans. The beams were normalized so that at least 95% of the volume of treatment (PTV) received the prescribed dose. The analysis was based on the comparison of changes of plans related to the dosimetric parameters, isodose distributions, hot spots and the number of monitor units (UM). In all variations of the planning, the goal of at least 95% of the PTV received the prescribed dose. The results suggest that the Convolution calculation algorithm overestimates the dose calculation for conformational radiotherapy planning 3D in prostate cases related to Superposition calculation algorithm. In the planning of 6 fields, the isodose distribution reached more healthy tissue when compared to the planning of 5 fields, as well as the hot spots were located outside the target volume treatment. The calculation of the number of UM by TPS XiO® is not affected by the choice of dose calculation algorithm during the planning. A practical guide was...

Junto ao avanço tecnológico nas técnicas de planejamento em radioterapia surgem métodos sofisticados de simulações de deposição de dose baseados em algoritmos de cálculo, a partir de Sistemas de Planejamento de Tratamento (TPS). É função dos físicos médicos atuantes na área se atualizarem aos novos processos e novas tecnologias ligadas ao TPS. O câncer de próstata é atualmente listado como o segundo tipo mais frequente em toda população masculina mundial e a radioterapia conformacional 3D é comumente utilizada para o tratamento destes casos. O objetivo deste trabalho foi avaliar diferentes planejamentos radioterápicos conformacionais 3D de casos de próstata, variando parâmetros radiométricos e algoritmos de cálculo, desenvolvidos no TPS XiO®, projetado pela Elekta. A partir de um único caso clínico de próstata selecionado, desenvolveram-se duas técnicas de planejamentos, com 5 e 6 campos, e para cada um variou-se a energia (6 MV e 10 MV) e o algoritmo de cálculo da dose (Superposition e Convolution), totalizando oito planos distintos. Os feixes foram normalizados para que ao menos 95% do volume de tratamento (PTV) recebesse a dose prescrita. A análise dos resultados baseou-se na comparação das variações dos planejamentos, em relação a parâmetros dosimétricos, distribuições de isodose, pontos quentes e o número de unidades monitoras (UM). Em todas as variações dos planejamentos foi alcançado o objetivo de ao menos 95% do PTV receber a dose prescrita. Os resultados sugerem que o algoritmo de cálculo Convolution superestima o cálculo de dose para planejamentos radioterápicos confomacionais 3D de casos de próstata, em relação ao algoritmo de cálculo Superposition. No planejamento de 6 campos, a distribuição de isodose alcançou mais tecido sadio que no planejamento de 5 campos, assim como, os pontos quentes se localizaram fora do volume alvo de tratamento. O cálculo do número de UM dos...
Keywords: Próstata - Câncer; Radioterapia; Análise numérica; Imagem tridimensional; Fisica medica; Numerical analysis